Role of NR1I2 (pregnane X receptor) polymorphisms in head and neck squamous cell carcinoma - Reuter, Tasmin; Warta, Rolf; Theile, Dirk; Meid, Andreas; Rigalli, Juan Pablo; Mogler, Carolin; Herpel, Esther; Grabe, Niels; Lahrmann, Bernd; Plinkert, Peter K.; Herold-Mende, Christel; Dyckhoff, Gerhard; et al. (Naunyn-Schmiedeberg's archives of pharmacology, 2015)
The pregnane X receptor (PXR) is a transcription factor regulating genes involved not only in pharmacokinetics but also in chemotherapy resistance and cancer progression. The significance of PXR for survival of head and neck squamous cell carcinoma (HNSCC) patients is unknown so far. Single nucleotide polymorphisms (SNPs) in the PXR-encoding NR1I2 gene influence receptor functionality and inducibility by ligands and thus modulate expression and activity of its target genes. In this study, seven SNPs in the NR1I2 gene were investigated for an association with PXR protein expression and survival of HNSCC patients. Genotyping was conducted using hybridisation probe format methodology. PXR protein expression was quantified by immunohistochemistry of tissue microarray samples of HNSCC biopsies. Genotypes were correlated to PXR protein expression by a linear model regressing on the continuous gene expression value and a Cox model regressing on overall survival times. Haplotype analysis was performed by reconstruction of haplotypes from genotype information according to the expectation-maximisation algorithm. Of all tested SNPs, rs1054190 and rs1054191 allele variants tended to correlate with a reduced protein expression score of PXR (p = 0.088). Four haplotypes, each consisting of two SNPs, rs3814055/rs1054190 and rs3814055/rs1054191 as well as rs1523127/rs1054190 and rs1523127/rs1054191, showed a significant reduction of the PXR expression score (p = 0.049 and p = 0.032). However, neither allele variants nor haplotypes influenced overall survival of the respective patients. Certain NR1I2 SNPs showed an impact on PXR protein expression in HNSCC but did not influence overall survival times, questioning their value as prognostic biomarkers.
Gesehen am 18.06.2020